Tamarixetin: A Promising Bioflavonoid Against Acetaminophen-Induced Liver Injury - Mehmet Ali Telafarlı; Ejder Saylav Bora; Firdes Topal; Oytun Erbaş (Current Issues in Molecular Biology, 2025)
Oxidative stress, mitochondrial dysfunction, and inflammatory responses cause acute liver failure in most cases of acetaminophen (APAP) overdose. Tamarixetin (Trx), an antioxidant and anti-inflammatory flavonoid, has not yet been studied in models of APAP-induced hepatotoxicity. Trx was tested for its protective effects on APAP-induced liver injury in rats using biochemical, histopathological, and oxidative stress parameters. Three groups of 30 male Wistar rats were randomly assigned to the following groups: control, APAP + Saline, and APAP + Trx (3 mg/kg/day, intraperitoneally for 3 days). A single 300 mg/kg intraperitoneal APAP dose caused hepatotoxicity. ALT, MDA, GSH, HSP-70, and thioredoxin were measured in blood and liver tissues. Liver sections were histopathologically examined. APAP depleted hepatic GSH and Trx and increased serum ALT and MDA. Trx treatment significantly reduced ALT (201.2 → 105.1 U/L), MDA (5.5 → 3.4 nmol/mg), and the percentage of histologically damaged hepatocytes (58.5% → 9.5%), while restoring GSH and thioredoxin levels. Notably, HSP-70 expression exceeded that of APAP and control levels, suggesting the modulation of the stress response. The Trx group showed significant hepatoprotection histologically. Trx reduces APAP-induced hepatic damage, likely through antioxidant and anti-inflammatory mechanisms. These findings suggest that Trx may be a natural hepatoprotectant, warranting clinical trials.